2005
DOI: 10.1002/eji.200526338
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondria-derivedN-formylated peptides are novel agonists equally active on FPR and FPRL1, whileListeria monocytogenes-derived peptides preferentially activate FPR

Abstract: N-formyl peptides are cleavage products of bacterial and mitochondrial proteins, and can attract leukocytes to sites of infection or tissue damage. In this study, HL-60 cell lines expressing the human N-formyl peptide receptor FPR or its two homologues (FPRL1, FPRL2) were used to determine the receptor selectivity of N-formylated peptides derived from Listeria monocytogenes or from human mitochondrial proteins. Bacterial peptides were 100-fold more potent on FPR than on FPRL1, whereas none of them could trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
167
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 40 publications
2
167
0
1
Order By: Relevance
“…Lens epithelial cells proliferate in the equatorial zones and elongate toward the anterior and posterior side of the lens, differentiating into lens fiber cells that form an onion-shaped structure. FPR1 could serve as a chemoattractant receptor guiding the elongation of lens epithelial cells in response to endogenous FPR1 ligands, such as mitochondrial peptides that have previously been reported to stimulate FPR1 (44). These peptides could be released from lens epithelial cells as they lose their organelles during differentiation to lens fiber cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lens epithelial cells proliferate in the equatorial zones and elongate toward the anterior and posterior side of the lens, differentiating into lens fiber cells that form an onion-shaped structure. FPR1 could serve as a chemoattractant receptor guiding the elongation of lens epithelial cells in response to endogenous FPR1 ligands, such as mitochondrial peptides that have previously been reported to stimulate FPR1 (44). These peptides could be released from lens epithelial cells as they lose their organelles during differentiation to lens fiber cells.…”
Section: Discussionmentioning
confidence: 99%
“…As proteins in the circulatory system are exposed to a variety of proteases and peptidases, plasma is rich in peptides of various size to constitute 'peptidome'. In this context, some endogeneous agonists of FPR and its variant receptors have been identified, such as the neutrophil granule protein cathepsin G (Sun et al, 2004), cleaved peptide from urokinase plasminogen activator receptor (Resnati et al, 2002), a fragment of heme-binding proteins (F2L) (Migeotte et al, 2005) and formylated peptides from mitochondria (Rabiet et al, 2005). In addition, a phospholipidbinding protein annexin I, which was reported to be a ligand for FPR and its variant receptors, has been implicated in promoting the invasiveness of a human intestinal cancer cell line and a mouse melanoma cell line (Babbin et al, 2006;Rondepierre et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, mice depleted of the FPR analogue mFPR1 were more susceptible to infection by Listeria monocytogenes (Gao et al, 1999) that produced high affinity mFPR1 agonist peptides (Southgate et al, 2008). Recently, a number of host-derived chemotactic agonists of FPR have been identified, including formylpeptides potentially released by mitochondria of ruptured cells (Rabiet et al, 2005), annexin I produced by activated epithelia (Xia et al, 2002) and a neutrophil granule protein, cathepsin G (Sun et al, 2004). In addition, functional FPR has been detected in cells of nonhaematopoietic origin, such as lung epithelial cells (Rescher et al, 2002) and hepatocytes (McCoy et al, 1995).…”
mentioning
confidence: 90%
“…1,5 Although The content of this publication do not necessarily reflect the views or policies of the Department of Health and Human Services, nor does the mention of trade names, commercial products, or organizations imply endorsement by the U.S. Government. the first agonist identified for FPR1 was bacterial formylated peptide, there are also a number of host-derived agonists including mitochondrial formyl peptides, 6 Annexin 1 (Anx A1) 7 and a neutrophil granule protein cathepsin G. 8 Therefore, FPR1 may be involved in pathophysiological processes in which its pathogen-derived or endogenous agonists are elevated. Studies further revealed that GBM cells undergoing necrosis release chemotactic agonist(s) that activate FPR1 in viable tumor cells.…”
mentioning
confidence: 99%